Bali cattle performance in the dry tropics of Sumbawa - Tanda Panjaitan; Geoffry Fordyce; Dennis Poppi (Indonesian Center for Animal Research and Development (ICARD), 2003)
Preliminary data on Bali cattle reproduction and growth presented is based on monitoring between August 2001 and August 2003 in the Sumbawa and Dompu Districts of Sumbawa Island, NTB. Sixty two % of calves were born between May and July inclusively. Inter-calving interval averaged 11.9 ±1.9 months; though recognized as an under-estimate, it still indicated of high fertility. Post-natal calf mortality was 5.3%. Birth, 6-, and 18-month weights of 14.2 ± 2.4 kg, 90 ± 20 kg, 172 ± 40 kg, respectively, were recorded. Average daily gains between birth to 6 months and from 6 to 18 months were 0.41 ± 0.11 and 0.23 ± 0.11 kg/d, respectively. Females reached mature size at 2.5-3.0 years at a mean weight of 237 kg and height of 1147 mm. Weight could be accurately predicted from chest girth: Weight (kg) = 7e0.0023 Chest girth (mm) (R2=0.9656). At the sites monitored, reproduction was high, and growth was typical for Bali cattle, indicating that these animals are well suited to the dry tropical environment of Sumbawa. Key words: Bali, weight, cattle, tropic